Patologías en bovinos y porcinos al examen post mortem en el camal de Latacunga - Sánchez Escobar, Paola Estefania (2021)
This investigation had as an objective to determine in a macroscopic way, the most common diseases on bovines and porcine in the postmortem exam in the Camal of Latacunga in the province of Cotopaxi, 407 animals were studied, by field method and the macroscopic observation technique, the data was saved in a document, where does the species, lot number, sex, and place of origin consists of. The population of the study was made by 277 bovines and 130 porcine, and as result, it was found that diseases do exist in the animals slaughtered in the Camal of Latacunga, among the most frequent in between the bovine species were Dystomatosis, Cirrhosis, Liver abscesses, Metritis, Pneumonia, Hydatidosis and Organs whit parasites, in the case of porcine the most common pathologies that were found, were the presence of parasites lesions and Hydatidosis. Of the sample of 277 bovine, 25 of them present some kind of disease, it was found that the 6.4% was parasite diseases and the 2.4% infectious diseases. In pigs, of 130 studied animals, 4 present pathologies and all of them was parasitic origin. By the place of origin, Latacunga is the city whit more cases 15 in total, 11 of parasite pathologies and 4 infection pathologies. Over pigs the total of found patolhologies were by parasites and from Latacunga.